Dimensions of Sociolinguistic Competence in English Language Communication of Indigenous People Students: An Exploratory Sequential Approach - Canoy, Fe T.; Baloran, Erick T. (RIRAI Publisher, 2025)
This study explored the dimensions of the sociolinguistic competence in English language communication of Tagakaolo senior high school students. Through purposive sampling, the participants of the study were the Tagakaolo senior high school students of the three secondary implementing units in the two municipalities of Davao Occidental. The exploratory factor analysis (EFA) yielded four factors: communication context, cultural knowledge, language learning, and language use. The model was found to be the best fit using confirmatory factor analysis (CFA) and other tests of fit indices. The final questionnaire, which was the main output of the study, consisted of 20 items and found to have good reliability based on its Cronbach’s alpha. Based on the results, the developed questionnaire will aid in determining the level of sociolinguistic competence in English language communication of Tagakaolo senior high school students, which can be used in future planning, policy making, and program implementations of different sectors.